Enhancing Literacy and Communicative Skills of Students With Disabilities in Special Schools Through Dialogic Literary Gatherings - Fernández-Villardón, Aitana; Valls-Carol, Rosa; Melgar Alcantud, Patricia; Tellado, Itxaso (Frontiers in Psychology, 2021)
Enhancing the quality of learning opportunities for students with disabilities and the learning level attained is a pending challenge. This challenge is especially relevant in the context of special schools, where the learning possibilities derived from interactions with others is limited. However, providing these students with a sufficient level of instrumental learning, such as literacy, and communicative and reasoning abilities is crucial for their subsequent educational and social opportunities. In this case study we analyse a special school that has implemented Dialogic Literary Gatherings with their students as a means to increase learning interactions within the group around the reading and debate of classical books. Semi-structured interviews were conducted with the school principal and with a teacher of the transition to adult life course, and two focus groups were conducted with teachers–one with primary education teachers and one with secondary education teachers–and two focus groups with students–one with primary education students and one secondary education and transition to adult life students–. On the one hand, results show the characteristics of the Dialogic Literary Gatherings that allowed these students to participate and learn. On the other hand, several improvements have been observed. First, regarding instrumental learning, students increased their motivation for reading, and improved their communicative and reasoning abilities and in their reading proficiency. Second, regarding students' behavior, conflict has reduced, solidarity attitudes have increased, and they have acquired dialogic and argumentative habits. Finally, at the emotional level, they gained self-esteem and confidence and feel more empowered to make their voice heard.